Individual and regional returns to higher education: empirical evidence for Germany - Berlingieri, Francesco (2017)
The thesis empirically investigates individual and regional returns of higher education in Germany. Chapter 2, coauthored with Ulrich Zierahn, investigates the individual payoffs of different fields of study. Graduates from Science, Technology, Engineering, and Mathematics (STEM) are usually found to have higher wages and a lower risk of overqualification. However, it is unclear whether we can interpret the effect of STEM subjects on overqualification and wages in a causal way, since individuals choosing these subjects might differ systematically in unobserved characteristics, such as ability. Using data on German male graduates we show that unobserved heterogeneity indeed matters for differences in the risk of overqualification and wages when STEM graduates are compared to the Business & Law group, while it plays only a minor role for the difference between STEM graduates and the Social Sciences & Humanities group. In Chapter 3, I investigate regional differences in skill mismatch depending on the size of the local labor market. Using survey data for Germany, I find that workers in large cities are both less likely to be overqualified for their job and to work in a different field than the one they are trained for. Different empirical strategies are employed to account for the potential sorting of talented workers into more urbanized areas. Results on individuals never moving from the place of childhood and fixed-effects estimates obtaining identification through regional migrants suggest that sorting does not fully explain the existing differences in qualification mismatch across areas. This provides evidence of the existence of agglomeration economies through better matches. However, lower qualification mismatch in larger cities is found to explain only a small part of the urban wage premium. Chapter 4, coauthored with Christina Gathmann and Verena Lauber, studies the effects of universities on the local economy using administrative data from Germany. Our empirical approach proceeds in two steps: first, we exploit college openings in order to identify the short- and medium-run effects on regional development. Second, we combine a matching procedure with a time-varying difference-in-differences approach to find suitable control regions for regions with a college opening. The results indicate that a college opening increases the share of high-skilled workers without reducing high-skilled wages which is consistent with shifts on the demand side.